Implementasi Manajemen Sumber Daya Manusia pada Divisi Human Capital Management PT Sinergi Gula Nusantara - Aisyah Arialma; Siti Aminah (Ikatan Da'i Indonesia, 2025)
Human resource management (HRM) is a crucial element in supporting organizational success. This study aims to analyze the implementation of HRM in the Human Capital Management Division of PT Sinergi Gula Nusantara. The research focuses on planning, development, and performance evaluation of employees to enhance organizational effectiveness. The research method employed is descriptive qualitative, using interviews, observations, and documentation for data collection. The findings indicate that the HRM implementation in this company aligns with standard practices, although challenges remain in optimizing employee training and development. This study provides recommendations to improve HRM strategies to sustainably achieve the company’s goals.